(untitled) (Homoeopathy for All, 2022)
We are seeing a shift in the needs and demands of the community in all spheres-political, social, educational, etc. All sections are looking for assured outcomes and are rewarding individuals and organizations which deliver what has been promised. The Digital world has made this process easy since data to arrive at decisions is readily tapped from the net. Educational organizations, for instance, have their rankings freely available.